Problematika Tiga Kota dalam Implementasi Kebijakan Pembatasan Sosial Berskala Besar (PSBB) Masa Pandemi Covid-19 (Studi Kasus: Jakarta, Surabaya, dan Bogor) - Yusuf Perdana; Ajeng Diah Kinanti; Feni Kurniawati; Syahna Ardani (JSHP : Jurnal Sosial Humaniora dan Pendidikan, 2021)
Covid-19 cases in Indonesia continue to increase sharply, the latest date is on July 22 2020 saw reactive patients reaching 91,751 cases, an increase there were 1,882 cases, deaths due to Covid-19 also increased by 139 people, the accumulative total of cases of death was 4,459 people. Assessment the effectiveness of government policies related to efforts to break the chain of transmission of Covid-19 continues to be carried out, including the implementation of social restriction policies large scale (PSBB) enforced in varios major cities in Indonesia. This study aims to analyze various conditions and problems implementation of large scale social restriction policies (PSBB) to allocating social assistance funds in the cities of Jakarta, Surabaya, and Bogor amidst unstable socio-economic conditions due to the Covid-19 pandemic refers to new habits in living everyday life, remembering these three big cities are cities with the intensity of socio-economic activities population with a heterogeneous background. Method which used in research is a qualitative method with collection techniques library data and interviews. The qualitative method is research which are descriptive in nature, using analysis, referring to data, utilize existing theory as supporting material, and produce a theory. The result of the study show that there are pros and cons to application this large scale social policy (PSBB), even the PSBB is considered useless and does not exist because there are still many fields that are still operating, distribution of social assistance funds that are considered a solution for the community many low income earners are still not on targetKeyword: Covid-19, PSBB, Jakarta, Surabaya, Bogor.ABSTRAKKasus Covid-19 di Indonesia terus meningkat tajam, data terbaru pada 22 Juli 2020 menunjukkan pasien yang reaktif mencapai 91.751 kasus, peningkatan terjadi sebanyak 1.882 kasus, kematian akibat Covid-19 juga meningkat 139 orang, total akumulatif kasus kematian menjadi 4.459 orang. Pengkajian kefektifan kebijakan pemerintah terkait upaya memutus rantai penularan Covid19 terus dilakukan, tak terkecuali pada penerapan kebijakan pembatasan sosial bersekala besar (PSBB) yang diberlakukan di berbagai kota besar di Indonesia. Penelitian ini bertujuan menganalisis berbagai kondisi serta problematika penerapan kebijakan pembatasan sosial bersekala besar (PSBB) hingga pemberian alokasi dana bantuan sosial di kota Jakarta, Surabaya, dan Bogor ditengah kondisi sosial ekonomi yang tidak stabil akibat pandemi Covid-19 yang merujuk pada kebiasaan baru dalam menjalani kehidupan sehari-hari, mengingat tiga kota besar ini merupakan kota dengan instensitas kegiatan sosial ekonomi yang padat dengan latar belakang penduduk yang heterogen. Metode yang digunakan dalam penelitian adalah metode kualitatif dengan teknik pengumpulan data kepustakaan serta wawacara. Hasil penelitian menunjukan adanya pro kontra terhadap penerapan kebijakan sosial bersekala besar (PSBB) ini, bahkan PSBB dianggap sia-sia dan tak ada karena masih banyaknya bidang-bidang yang tetap beroperasi, penyaluran dana bantuan sosial yang dianggap solusi bagi masyarakat berpenghasilan rendah pun masih banyak yang tak tepat sasaran.Kata Kunci: Covid-19, PSBB, Jakarta, Surabaya, Bogor.